Casein kinase 2-dependent serine phosphorylation of MuSK regulates acetylcholine receptor aggregation at the neuromuscular junction. - Cheusova, Tatiana; Khan, Muhammad A.; Schubert, Steffen; Gavin, Anne-Claude; Buchou, Thierry; Jacob, Germaine; Sticht, Heinrich; Allende, Jorge; Boldyreff, Brigitte; Brenner, Hans Rudolf; Hashemolhosseini, Said (Genes & Development, 2006)
The release of Agrin by motoneurons activates the muscle-specific receptor tyrosine kinase (MuSK) as the main organizer of subsynaptic specializations at the neuromuscular junction. MuSK downstream signaling is largely undefined. Here we show that protein kinase CK2 interacts and colocalizes with MuSK at post-synaptic specializations. We observed CK2-mediated phosphorylation of serine residues within the kinase insert (KI) of MuSK. Inhibition or knockdown of CK2, or exchange of phosphorylatable serines by alanines within the KI of MuSK, impaired acetylcholine receptor (AChR) clustering, whereas their substitution by residues that imitate constitutive phosphorylation led to aggregation of AChRs even in the presence of CK2 inhibitors. Impairment of AChR cluster formation after replacement of MuSK KI with KIs of other receptor tyrosine kinases correlates with potential CK2-dependent serine phosphorylation within KIs. MuSK activity was unchanged but AChR stability decreased in the presence of CK2 inhibitors. Muscle-specific CK2β knockout mice develop a myasthenic phenotype due to impaired muscle endplate structure and function. This is the first description of a regulatory cross-talk between MuSK and CK2 and of a role for the KI of the receptor tyrosine kinase MuSK for the development of subsynaptic specializations. © 2006 by Cold Spring Harbor Laboratory Press.
UnivIS-Import:2015-03-09:Pub.2006.med.IB.LPCIPDBI.casein
Keywords: Casein kinase; CK2; MuSk; Neuromuscular junction; Skeletal muscle; Synapse